Nilai Hospitalitas Kristen dalam Budaya Raputallang Pada Suku Toraja dan Relevansinya Terhadap Pencegahan Konflik - Milkia, Milkia; Pateta, Nidya Elgidya Amara; Palimbong, Yulita (SEKOLAH TINGGI TEOLOGI STAR'S LUB LUWUK BANGGAI, 2023)
Social conflict often has a very negative impact on the community because it needs prevention efforts. One way is to develop the values of hospitality that exist in society. The Toraja people in South Sulawesi have hospitality values that live in the Raputallang culture. Hospitality values are very strong with Christian values. This study aims to explore the extent to which the relevance of Raputalllang's hospitality values is in preventing the emergence of social conflict in society. The research method used is a literature study of several published writings about Raputalllang culture. The study results show that Raputallang's hospitality values have four functions: problem-solving, self-introspection, social bonding, and social control. These four functions encourage every member of the Toraja community to continue to improve their ability to live in harmony with others in the midst of living together. This ability contributes to the prevention of social conflict in society.